Predictive factors of a viral neutralizing humoral response after a third dose of COVID‐19 mRNA vaccine. Issue 5 (21st February 2022) - Charmetant, Xavier; Espi, Maxime; Barba, Thomas; Ovize, Anne; Morelon, Emmanuel; Mathieu, Cyrille; Thaunat, Olivier
Abstract : Kidney transplant recipients (KTRs) have reduced ability to mount adequate antibody response after two doses of the COVID‐19 mRNA vaccine. French health authorities have allowed a third booster dose (D3) for KTRs, but their response is heterogeneous and tools able to discriminate the responders are lacking. Anti‐RBD IgG titers (chemiluminescence immunoassay), spike‐specific cellular responses (IFN‐γ‐releasing assay, IGRA), and in vitro serum neutralization of the virus (the best available correlate of protection), were evaluated 7–14 days after the second dose (D2) of BNT162b2 vaccine in 93 KTRs. Among the 73 KTRs, whose serum did not neutralize SARS‐CoV‐2 in vitro after D2, 14 (19%) acquired this capacity after D3, and were considered as "responders." Exploratory univariate analysis identified short time from transplantation and high maintenance immunosuppression as detrimental factors for the response to D3. In addition, any of the presence of anti‐RBD IgGs and/or positive IGRA after D2 was predictive of response to D3. By contrast, none of the KTRs with both a negative serology and IGRA responded to D3. In summary, routinely available bioassays performed after D2 allow identifying KTRs that will respond to a booster D3. These results pave the way for the personalization of vaccination strategy in KTRs. Abstract : The generation of a protective virus‐neutralizing humoral response after a third dose of SARS‐CoV‐2 mRNA vaccine (BNT162b2) is heterogeneous among kidney transplant recipients that fail to respond to the standard two‐dose regimen but can be predicted by monitoring antibody and cellular responses after the second dose.